2019
DOI: 10.1007/s00436-019-06339-1
|View full text |Cite
|
Sign up to set email alerts
|

How effective is freezing at killing Anisakis simplex, Pseudoterranova krabbei, and P. decipiens larvae? An experimental evaluation of time-temperature conditions

Abstract: The consumption of raw or inadequately cooked marine fish can lead to several disorders caused by the ingestion of viable anisakid nematodes. Although anisakid larvae can be killed by subzero temperatures, making freezing an important control measure for this potential health hazard, these parasites can survive freezing under some conditions. Therefore, the aim of the present study was to experimentally evaluate the time-temperature conditions needed to kill Anisakis simplex and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 32 publications
1
18
0
1
Order By: Relevance
“…Improving molecular knowledge on this family of parasites may be helpful in several ways, spanning from basic research to clinical and public health applications. These are mostly related to: (i) food-safety, given the presence of infective larvae in food products [ 26 , 27 ]; (ii) allergy-mediated diseases, even in relation to work exposure or to potential therapeutic use of parasitic derived products [ 28 ]; and (iii) the understanding of carcinogenic processes in relation to nematode infection [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Improving molecular knowledge on this family of parasites may be helpful in several ways, spanning from basic research to clinical and public health applications. These are mostly related to: (i) food-safety, given the presence of infective larvae in food products [ 26 , 27 ]; (ii) allergy-mediated diseases, even in relation to work exposure or to potential therapeutic use of parasitic derived products [ 28 ]; and (iii) the understanding of carcinogenic processes in relation to nematode infection [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…decipiens [ 43 ] and P . krabbei [ 110 ]. While the term “anisakiosis” refers to the pathology caused specifically by the species Anisakis simplex s.s. [ 7 , 14 , 15 , 19 , 20 , 52 , 89 ].…”
Section: Anisakiosis/anisakiasismentioning
confidence: 99%
“…To prevent anisakiasis, many countries, such as countries in the European Union (EU), United States of America (USA), and Canada, require the freezing of raw fish before placing on the market or other processing to kill viable parasite larvae [ 10 ]. However, it should be emphasized that, according to the published studies, single A. simplex larvae can survive at −20 °C for 24 h [ 10 ] and, according to other studies, even up to 60 h [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…To prevent anisakiasis, many countries, such as countries in the European Union (EU), United States of America (USA), and Canada, require the freezing of raw fish before placing on the market or other processing to kill viable parasite larvae [ 10 ]. However, it should be emphasized that, according to the published studies, single A. simplex larvae can survive at −20 °C for 24 h [ 10 ] and, according to other studies, even up to 60 h [ 11 ]. Interestingly, Sanchez-Alonso et al [ 12 ] showed that A. simplex L3 larvae during freezing release more allergens than the larvae not exposed to low temperatures, which can increase the allergic potential of frozen seafood containing Anisakis .…”
Section: Introductionmentioning
confidence: 99%